2016
DOI: 10.1111/sms.12817
|View full text |Cite
|
Sign up to set email alerts
|

Postactivation potentiation can counteract declines in force and power that occur after stretching

Abstract: Stretching can decrease a muscle's maximal force, whereas short but intense muscle contractions can increase it. We hypothesized that when combined, postactivation potentiation induced by reactive jumps would counteract stretch-induced decrements in drop jump (DJ) performance. Moreover, we measured changes in muscle twitch forces and ankle joint stiffness (K ) to examine underlying mechanisms. Twenty subjects completed three DJs and 10 electrically evoked muscle twitches of the triceps surae subsequent to four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 47 publications
(118 reference statements)
0
19
0
Order By: Relevance
“…In fact, the extent of potentiation for contractile properties ranged from 4 to 188% immediately after the conditioning contraction, with a progressive decline over time ([ 14 , 19 , 21 , 24 26 ]; Table 1 ).…”
Section: Background and Putative Approaches To Examine Postactivationmentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, the extent of potentiation for contractile properties ranged from 4 to 188% immediately after the conditioning contraction, with a progressive decline over time ([ 14 , 19 , 21 , 24 26 ]; Table 1 ).…”
Section: Background and Putative Approaches To Examine Postactivationmentioning
confidence: 99%
“… CC conditioning contraction Specifications based in the relevant literature ([ 9 , 14 16 , 18 , 19 , 21 , 24 26 , 36 , 53 , 56 ]) …”
Section: Background and Putative Approaches To Examine Postactivationmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to improving jump and sprint performances [5,6,17,18,23,29], PAP induced by performing plyometric exercises has also been reported to improve throwing (shot put, hammer throw, discus and javelin) [16] and judo performances [20]. It has even been suggested that that plyometric might be more effective than a traditional resistance exercise in inducing PAP as plyometric exercises are associated with preferential recruitment of type II motor units, which is the mechanism underpinning PAP [25].…”
Section: Introductionmentioning
confidence: 99%